2017
DOI: 10.1016/j.nutres.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil supplementation benefits the murine host during the acute phase of a parasitic infection from Trypanosoma cruzi

Abstract: Long-chain omega-3 polyunsaturated fatty acids (LC n-3 PUFA) are known to modulate a variety of immune cell functions. On occasion, this has led to diminished host resistance to certain viral and bacterial infections. Little is known about the impact of n-3 PUFA on host resistance to parasitic infection, however, based on results from a small study conducted more than two decades ago, we hypothesized that providing mice LC n-3 PUFA will diminish host resistance to Trypanosoma cruzi, the parasitic pathogen resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The heart was fixed in 10% buffered formalin for histological analysis. Spleen cells were cultured with medium or total antigen of T. cruzi (TcAg) as previously described ( 38 ), and the supernatants were stored for the quantification of nitrite, cytokines, and prostaglandin E 2 (PGE 2 ) (Cayman, Ann Arbor, MI, USA). The 12th day after infection was chosen during this phase, NO production is elevated, the cells of the acquired immune response are already activated, and the host response begins to control parasitemia ( 39 41 ).…”
Section: Methodsmentioning
confidence: 99%
“…The heart was fixed in 10% buffered formalin for histological analysis. Spleen cells were cultured with medium or total antigen of T. cruzi (TcAg) as previously described ( 38 ), and the supernatants were stored for the quantification of nitrite, cytokines, and prostaglandin E 2 (PGE 2 ) (Cayman, Ann Arbor, MI, USA). The 12th day after infection was chosen during this phase, NO production is elevated, the cells of the acquired immune response are already activated, and the host response begins to control parasitemia ( 39 41 ).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Otta et al (2018) showed that K777 the extract lead compound induces prominent proinflammatory responses modulation by interleukin -10-positive CD4 + /CD8 + T cells and this contributed to the protection against the Chagas disease. In addition, diet supplementation with fish oil led to increase the resistance to T. cruzi infection through modulating various immunological factors ( Lovo-Martins et al, 2017 ).…”
Section: Host-targeted Therapeutics and Approaches For Treatment Of Cmentioning
confidence: 99%
“…Previous studies demonstrated that ω3 and ω6 PUFAs impacted cellular and innate immunity ( 109 , 110 ). These PUFAs also affected the survival of mice following an experimental T. cruzi infection and showed fewer indications during the acute phase of this parasitic infection ( 111 ). The mechanisms for this protection are shown in Figure 4 .…”
Section: Parasitic Diseases and Their Available Treatmentsmentioning
confidence: 99%
“…During the acute form of T. cruzi infection, the increased level of prostaglandin E2 (PGE2) results in temporary immunosuppression, which leads to decreased production of TNF-α by the host ( 112 ). The immune cells from the omega-PUFAs diet lowered PGE2 amounts and consequently increased the level of TNF-α leading to decreased parasitemia ( 111 ). PGE2, Prostaglandin E2; TXA 2 , thromboxane A2; GM-CSF, Granulocyte-macrophage colony-stimulating factor; TNF-α, Tumor necrosis factor-alpha.…”
Section: Parasitic Diseases and Their Available Treatmentsmentioning
confidence: 99%